Auto-ségrégation résidentielle et ordre urbain chez les classes moyenne et supérieure à Mexico : une question d’échelle ? - Guénola Capron (L'Espace Politique, 2012)
The issue of this paper is to focus on the spatial and social scale of urban enclaves, enclosures and securization, for a better understanding of the phenomenon at stake in autosegregation and confinement of middle and upper Latin-American classes: both the extent of the facts, the size of the gated communities, the problems, the challenges and problems behind its spatial concentration. More than communitarian spirit, gated communities and its spatial concentrations aim to produce urban order in a scale that goes over the residential scale and which implies important changes in conception of urban solidarity.